The Palgrave Handbook of Sociology in Britain
XIII, 631 p.
Keywords: Leading sociologists outline the historical development of the discipline in Britain and document its continuing influence in this essential and comprehensive reference work. Spanning the Scottish enlightenment of the 18th century to the present day this Handbook maps the discipline and the British contribution.